EPIDEMIOLOGICAL FEATURES OF MALIGNANT TUMORS OF FEMALE REPRODUCTIVE ORGANS IN THE REPUBLIC OF KARAKALPAKSTAN - Madenbaeva G.I; Matnazarova G.S; Kurbaniyazova M.O; Khamzayeva N.T; Kurbanbayeva B.R (Scholar Express Journals, 2024)
Breast cancer (BC) is one of the pressing medical and social problems of modern oncology due to its prevalence and psychological aspects associated with the problems of social adaptation of women. [1,2] According to IARC estimates, 14.1 million new cases of malignant neoplasms and 8.2 million deaths from them were diagnosed worldwide in 2012. Breast cancer was diagnosed in 1.6 million women, of which 47.3% (74.1 0 /0000) were in developed countries and 52.7% (31.3 0 /0000) in developing countries. In recent decades, there has been a continuing trend towards an increase in morbidity rates both in developed (1.0–2.0% per year) and in developing countries [3]. The geography of breast cancer distribution in the world is not uniform [219]. High incidence rates are observed in Canada (79.8 0 /0000), Israel (80.5 0 /0000), the USA (92.9 0 /0000) and Western European countries (90.0 0 /0000), in particular Belgium (111.9 0 /0000). Low incidence rates are observed on the African continent (36.2 0 /0000), which is explained by low life expectancy and unreliability of medical statistics. The fight against cancer is currently one of the main tasks of healthcare in many countries of the world. To organize it, it is necessary to conduct epidemiological studies, since the oncological situation in a certain territory depends on regional specifics, including a set of factors associated with both the external environment and demographic processes and sociobiological characteristics of the population. Malignant tumors of the mammary gland, occupying leading positions in determining the level of temporary and permanent loss of working capacity, reduce the average life expectancy of the female population, cause irreparable economic damage to society [4,5]. Untimely diagnosis, a high proportion of patients with an advanced tumor process (31.9%), high one-year mortality (7.4%) [6] determine the importance of measures for the early diagnosis of this disease - detection of precancerous and tumor pathology of the mammary gland in the early stages of the disease for their timely treatment.
Keywords: Breast cancer; 10-year morbidity by age group